Beat The Course of Impaired Water and Salt Metabolism in Patients with Heart Failure - Shakhobidinov X.Sh.; Usmanova D. N.; Bеktasheva G.M. (Scholars Digest Publishing, 2023)
To study the relationship between violations of water-salt homeostasis upon admission to the hospital in patients hospitalized for decompensation of CHF, III–IV FC according to the NYHA classification and a long-term annual prognosis. This prospective follow-up study is based on clinical and anamnestic data and the results of a one-year follow–up of 111 patients – study participants hospitalized for decompensation of CHF in GBUZ City Clinical Hospital No. 24 DZM in January 2015 - February 2016. In patients hospitalized with decompensation of CHF, in the presence of violations of water-salt homeostasis upon admission to the hospital, the relative risk of annual mortality increased by 1.43 times by the end of the follow–up year (HR=1.43; 95% CI: 1.10-1.87; p<0.01) compared with patients who had normal levels of sodium and potassium in blood on admission.
Keywords: acute decompensation of HF, pathogenesis, hyponatremia, hypokalemia, hyperkalemia, prognosis.